PENGARUH UKURAN PERUSAHAAN, KEBERADAAN KOMITE AUDIT DAN LEVERAGE TERHADAP AUDIT DELAY - Pion Janartha, I Wayan; Suprasto H., Bambang (E-Jurnal Akuntansi, 2016)
This research aimed to get empirically the effect of firm size, the existence of an audit committee and leverage to audit delay. The theory used in this research is the Positive Accounting Theory and Signaling Theory. The population used in this study are all companies listed on the Stock Exchange the period of 2012 through 2014 as many as 502 companies. The samples using the technique is non-random sampling, and the sampling method used in this research is purposive sampling method. The data collection by documentation. The data analysis technique used in this research is multiple linear regression. The results of this research showed that the size of the company negatively affect on audit delay. Variable existence of audit committee positively affects on audit delay. While Leverage does not affect the audit delay.
Keywords: the size of the company; the existence of an audit committee; leverage; audit delay